Polyketides from the marine mangrove-derived fungus Aspergillus ochraceus MA-15 and their activity against aquatic pathogenic bacteria. (June 2015) - Liu, Yang; Li, Xiao-Ming; Meng, Ling-Hong; Wang, Bin-Gui
Graphical abstract: Highlights: Aspergillus ochraceus MA-15, a mangrove-derived rhizospheric fungus, was studied. Three new polyketides and 12 related derivatives were isolated and identified. Six compounds showed inhibitory activity against tested aquatic pathogenic bacteria. Abstract: Three new polyketides, namely, asperochrins A–C (1 –3 ), along with 12 known related derivatives (4 –15 ), were isolated from Aspergillus ochraceus MA-15, a fungus obtained from the rhizospheric soil of marine mangrove plant Bruguiera gymnorrhiza . The structures of these compounds were elucidated on the basis of spectroscopic analysis and the absolute configurations of the new compounds were determined by CD experiments and modified Mosher's method. The X-ray crystallographic experiment of compound 4 disclosed its racemic nature as (±)-botryoisocoumarin A for the first time. The brine shrimp lethality and antibacterial activity of compounds 1 –15 were evaluated. Compounds 1, 5, 6, 9, 11, and 15 showed inhibitory activity against aquatic pathogenic bacterial Aeromonas hydrophila, Vibrio anguillarum, and Vibrio harveyi .